PENGARUH MENGKONSUMSI TUAK TERHADAP EROSI GIGI PADA MASYARAKAT TAMBUNAN LUMBAN GAOL KABUPATEN TOBA SAMOSIR - sondang; Asnita Bungaria Simaremare (Poltekkes Kemenkes Medan, 2023)
Tuak is a typical drink of Batak Toba society made from Nira which is fermented with raru, yeast, a kind of bark of tree.Erosion of teeth is defined as the loss of the hard tissue of the teeth as a result of chemical processes that does not involve bacteria. This research method of this study is analytic method with cross sectional study design, the sample of this study is 60 people of Tambunan Lumban Gaol of Toba Samosir District. The samples were taken by using purposive sampling technique. The collection of the data was done by direct examination and questionnaire filled out by the respondents. Data analysis was processed by statistical test using chi-square. This study showed that the weekly frequency of consuming tuak and the duration of drinking tuak had a significant effect on tooth erosion that can be seen from the data of p = 0,0001 and p = 0,002, there were 30 respondents (50%) had severe dental erosion, 13 respondents (21.6%) had moderate dental erosion, 12 respondents (20%) had mild dental erosion 5 respondents (8.3%) had healthy dental erosion. The result of chi-square test shows that the null hypothesis (HO)is tuak and the duration of consuming tuak towards the erosion of teeth in Tambunan Gaol Community of Toba Samosir District. This study concluded that the weekly frequency of drinking of tuak and the duration of consuming tuak gives effects to the dental erosion.